The Effects of Percentage-Based, Rating of Perceived Exertion, Repetitions in Reserve, and Velocity-Based Training on Performance and Fatigue Responses - Cowley, Nicholas; Nicholson, Vaughan; Timmins, Ryan; Munteanu, Gabriella; Wood, Tandia; García-Ramos, Amador; Owen, Cameron; Weakley, Jonathon (Journal of strength and conditioning research, 2025)
Cowley, N, Nicholson, V, Timmins, R, Munteanu, G, Wood, T, García-Ramos, A, Owen, C, and Weakley, J. The effects of percentage-based, rating of perceived exertion, repetitions in reserve, and velocity-based training on performance and fatigue responses. J Strength Cond Res 39(4): e516-e529, 2025-This study assessed the effects of percentage-based training (%1RM), rating of perceived exertion (RPE), repetitions in reserve (RIR), and velocity-based training (VBT) on (a) acute kinematic outputs, perceptions of effort, and changes in neuromuscular function during resistance training; and (b) neuromuscular fatigue and perceptions of soreness 24 hours after exercise. In a randomized crossover design, 15 subjects completed a %1RM, RPE, RIR, and VBT training condition involving a fatiguing protocol followed by 5 sets of the free-weight back squat and bench press at 70% of 1 repetition maximum. Subjects returned at 24 hours to assess neuromuscular fatigue and perceived soreness. Percentage-based training and RPE allowed the smallest volume loads, with %1RM prescription causing sets to be regularly taken to failure. Alternatively, RIR and VBT allowed greater maintenance of training volume. Velocity-based training had the most accurate training prescription, with all sets being within 5% of the intended starting velocity, while the RPE and %1RM prescriptive methods caused subjects to train with loads that were increasingly inaccurate. The RPE prescriptive method had the lowest reported values for differential RPE while the %1RM had the greatest change across the session. At no point were there between-group differences in measures of neuromuscular fatigue or perceived soreness. These findings demonstrate that autoregulatory prescriptive methods can be used to mitigate the risk of training to failure, ensure accurate training prescription that can maintain training volume, and enhance within-training kinematic outputs without altering neuromuscular fatigue or perceptions of soreness.